Method for producing non-aqueous electrolyte secondary battery, slurry for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

By using a high dielectric constant and low viscosity solvent in the electrode active material layer of the non-aqueous electrolyte secondary battery, the problem of reduced discharge capacity of the battery during large current discharge is solved, the output characteristics and cycle characteristics are improved, and more efficient is achieved battery performance.

CN119325663APending Publication Date: 2025-01-17KYOCERA CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380044897.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-29
Filing Date
2023-08-18
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The conventional non-aqueous electrolyte secondary battery cannot adequately suppress the reduction of discharge capacity when discharged at a high current, and there is room for improvement in the output characteristics.

Method used

By using a high dielectric constant and low viscosity solvent as the solvent for the non-aqueous electrolyte in the electrode active material layer, the output characteristics are improved, and the proportion and composition of the solvent in the electrode slurry layer are controlled to ensure the structure of the electrode active material layer. and performance.

Benefits of technology

It is possible to improve the output characteristics and cycle characteristics of non-aqueous electrolyte secondary batteries while maintaining high capacity, and extend the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119325663A_ABST
    Figure CN119325663A_ABST
Patent Text Reader

Abstract

A non-aqueous electrolyte secondary battery, a method for manufacturing the same, and a slurry suitable for forming an electrode slurry layer of the non-aqueous electrolyte secondary battery, the non-aqueous electrolyte secondary battery having a positive electrode slurry layer, a separator, and a negative electrode slurry layer in this order, the positive electrode slurry layer is configured from a slurry in which a positive electrode active material is dispersed in a non-aqueous electrolyte solution containing a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPas, and the negative electrode slurry layer is configured from a slurry in which a negative electrode active material is dispersed in a non-aqueous electrolyte solution containing a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing a non-aqueous electrolyte secondary battery, slurry for the non-aqueous electrolyte secondary battery and the non-aqueous electrolyte secondary battery. Background Art

[0002] The non-aqueous electrolyte secondary battery has a structure in which a positive electrode collector, a positive electrode active material layer, a separator, a negative electrode active material layer and a negative electrode collector are stacked in sequence. The space between the positive electrode active material layer and the negative electrode active material layer is filled with a non-aqueous electrolyte and separated by a separator. The separator has pores and acts as a positive-negative electrode separation membrane that insulates the positive and negative electrodes while allowing non-aqueous electrolyte and ions to pass through under normal battery usage conditions. Charging and discharging can be performed by allowing ions to move back and forth between the positive and negative electrodes. Currently, lithium-ion secondary batteries are widely used, and lithium ions move back and forth between the positive and negative electrodes to be repeatedly charged and discharged.

[0003] Research is underway to increase the capacity of non-aqueous electrolyte secondary batteries. For example, Patent Document 1 describes an electrochemical battery comprising:

[0004] a positive electrode comprising a first active material and an electrolyte in a first non-aqueous liquid electrolyte and being composed of a non-adhesive body;

[0005] a negative electrode comprising a second active material and an electrolyte in a second non-aqueous liquid electrolyte and being composed of a non-binding body; and

[0006] The ion permeable membrane is disposed between the positive electrode and the negative electrode, wherein

[0007] The positive electrode and the negative electrode each have a thickness of about 200 μm to about 3000 μm.

[0008] According to the technology described in Patent Document 1, the electrode active material layer (positive electrode active material layer and negative electrode active material layer) is in a non-bonded state, as in the positive electrode and negative electrode mentioned above. Therefore, a thick film can be made while maintaining the flexibility of the electrode active material layer, and there is no need for an adhesive to bond the solid particles together. This allows the battery to maintain its flexibility while significantly increasing its charge capacity and overall energy density.

[0009] Previous technical literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2017-147222 Summary of the invention

[0012] Technical issues to be solved by the invention

[0013] The inventor has repeatedly studied a battery (also referred to as a "quasi-solid-state secondary battery" in this specification) that has achieved high capacity by setting the electrode active material layer as an electrode slurry layer formed by dispersing the electrode active material in a non-aqueous electrolyte as described in patent document 1. As a result, it is known that the high capacity of the battery can be achieved according to the structure of the quasi-solid-state secondary battery, but the reduction of the discharge capacity cannot be fully suppressed when a large current discharge is performed, and there is room for improvement in output characteristics. The results of the study conducted in order to solve this problem show that the output characteristics can be improved by including a solvent with a high dielectric constant and a low viscosity as a solvent for a non-aqueous electrolyte, but the use of a solvent with a high dielectric constant and a low viscosity in a non-aqueous electrolyte will produce a new problem that the discharge capacity is easily reduced as the charge and discharge are repeatedly performed.

[0014] The present invention relates to a non-aqueous electrolyte secondary battery that realizes high capacity by setting an electrode active material layer as an electrode slurry layer formed by dispersing an electrode active material in a non-aqueous electrolyte, and the subject is to provide a method for manufacturing a non-aqueous electrolyte secondary battery that can improve the output characteristics of the obtained non-aqueous electrolyte secondary battery and can also fully improve the cycle characteristics, and a non-aqueous electrolyte secondary battery that can improve the output characteristics and also fully improve the cycle characteristics. In addition, the subject of the present invention is to provide a slurry suitable for forming the electrode slurry layer of the above-mentioned non-aqueous electrolyte secondary battery.

[0015] Means for solving technical problems

[0016] The above-mentioned problems of the present invention are solved by the following means.

[0017] [1]

[0018] A method for manufacturing a non-aqueous electrolyte secondary battery, comprising the following (a1) to (c1):

[0019] (a1) obtaining a positive electrode layer member composed of a laminate of a positive electrode current collector and a positive electrode slurry layer in which a positive electrode active material is dispersed in a non-aqueous electrolyte solution at least part of which is a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s;

[0020] (b1) forming a laminated structure of a negative electrode current collector and a negative electrode slurry layer in which a negative electrode active material is dispersed in a non-aqueous electrolyte solution having a relative dielectric constant of less than 5.0 and / or a viscosity of 2.0 mPa·s or more, and obtaining a negative electrode layer component consisting of a laminate of the negative electrode current collector and the negative electrode slurry layer by making the negative electrode slurry layer contain a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s; and

[0021] (c1) The positive electrode layer member, the separator, and the negative electrode layer member are stacked to form a stacked structure such that one side of the separator is in contact with the positive electrode slurry layer and the other side of the separator is in contact with the negative electrode slurry layer.

[0022] [2]

[0023] A method for manufacturing a non-aqueous electrolyte secondary battery, comprising the following (a2) to (c2):

[0024] (a2) obtaining a positive electrode layer member composed of a laminate of a positive electrode current collector and a positive electrode slurry layer in which a positive electrode active material is dispersed in a non-aqueous electrolyte solution having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s at a ratio of X mass % of a solvent in the solvent;

[0025] (b2) obtaining a negative electrode layer member composed of a negative electrode current collector and a negative electrode slurry layer formed by dispersing a negative electrode active material in a non-aqueous electrolyte solution in which the ratio of a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s in the solvent is less than the above X mass %; and

[0026] (c2) The positive electrode layer member, the separator, and the negative electrode layer member are stacked to form a stacked structure such that one side of the separator is in contact with the positive electrode slurry layer and the other side of the separator is in contact with the negative electrode slurry layer.

[0027] 〔3〕

[0028] The method for producing a non-aqueous electrolyte secondary battery according to [1] or [2], wherein:

[0029] In the laminated structure formed by the above (c1) and (c2), the thickness of the positive electrode slurry layer is 150 μm or more.

[0030] [4]

[0031] The method for producing a non-aqueous electrolyte secondary battery according to any one of [1] to [3], wherein:

[0032] The solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s includes a compound having at least one of a cyano group, an ester bond, and an ether bond.

[0033] 〔5〕

[0034] The method for manufacturing a non-aqueous electrolyte secondary battery according to [4], wherein:

[0035] The compound having at least one of a cyano group, an ester bond, and an ether bond is a compound represented by any one of the following formulae (1) to (3).

[0036] [Chemical formula 1]

[0037]

[0038] In the above formula, R 11 ~R 14 represents an alkyl group having 1 to 3 carbon atoms. 15 represents a hydrogen atom or a fluorine atom. n is an integer from 1 to 3. In the above formula (2), the two R 12 In the above formula (3), R 13 and R 14 They can be connected to each other to form a ring.

[0039] [6]

[0040] The method for producing a non-aqueous electrolyte secondary battery according to any one of [1] to [5], wherein:

[0041] In the above (a1) and (a2), the ion conductivity of the non-aqueous electrolyte constituting the positive electrode slurry layer is set to 12 mS / cm or more.

[0042] 〔7〕

[0043] The method for producing a non-aqueous electrolyte secondary battery according to any one of [1] to [6], wherein:

[0044] The content of the electrolyte in the nonaqueous electrolyte solution constituting the positive electrode slurry layer in (a1) and (a2) and the content of the electrolyte in the nonaqueous electrolyte solution constituting the negative electrode slurry layer in (b1) and (b2) are set to 0.9 M or more.

[0045] [8]

[0046] The method for producing a non-aqueous electrolyte secondary battery according to any one of [1] to [7], wherein:

[0047] The nonaqueous electrolyte solution constituting the positive electrode slurry layer in (a1) and (a2) and the nonaqueous electrolyte solution constituting the negative electrode slurry layer in (b1) and (b2) contain an additive that reacts with the surface of the negative electrode active material to form a film.

[0048] 〔9〕

[0049] The method for manufacturing a non-aqueous electrolyte secondary battery according to [8], wherein:

[0050] The content of the additive in the nonaqueous electrolyte solution constituting the positive electrode slurry layer and the nonaqueous electrolyte solution constituting the negative electrode slurry layer is set to 2 to 28% by mass.

[0051] 〔10〕

[0052] The method for producing a non-aqueous electrolyte secondary battery according to any one of [2] to [9], wherein:

[0053] In the negative electrode slurry layer in (b2), the ratio of the solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s in the solvent is set to less than 20 mass %.

[0054]

[11]

[0055] A method for manufacturing a non-aqueous electrolyte secondary battery according to any one of [1] to

[10] , comprising: after the above (c1) and the above (c2), performing CV charging at a potential higher than the reduction potential of the above solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s.

[0056]

[12]

[0057] The method for producing a non-aqueous electrolyte secondary battery according to any one of [1] to

[11] , wherein:

[0058] The positive electrode slurry layer and the negative electrode slurry layer of the obtained non-aqueous electrolyte secondary battery both contained acetonitrile.

[0059] 〔13〕

[0060] A slurry for a non-aqueous electrolyte secondary battery comprises: a non-aqueous electrolyte containing a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s; and an electrode active material.

[0061]

[14]

[0062] The slurry for non-aqueous electrolyte secondary batteries according to

[13] , wherein

[0063] The electrode active material is a positive electrode active material, and the ratio of the solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s in the solvent is 8 mass % or more.

[0064] 〔15〕

[0065] The slurry for non-aqueous electrolyte secondary batteries according to

[13] , wherein

[0066] The electrode active material is a negative electrode active material, and the ratio of the solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s in the solvent is less than 20 mass %.

[0067]

[16]

[0068] The slurry for non-aqueous electrolyte secondary batteries according to any one of

[13] to

[15] , wherein

[0069] The content of the electrode active material in the slurry is 40% by volume or more.

[0070]

[17]

[0071] The slurry for non-aqueous electrolyte secondary batteries according to any one of

[13] to

[16] , wherein

[0072] The solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s includes acetonitrile.

[0073]

[18]

[0074] The slurry for non-aqueous electrolyte secondary batteries according to any one of

[13] to

[17] is used to form an electrode slurry layer of a non-aqueous electrolyte secondary battery.

[0075]

[19]

[0076] A non-aqueous electrolyte secondary battery comprises a positive electrode slurry layer, a separator and a negative electrode slurry layer in sequence, wherein:

[0077] The positive electrode slurry layer is composed of a slurry in which a positive electrode active material is dispersed in a non-aqueous electrolyte solution containing a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s.

[0078] The negative electrode slurry layer is composed of a slurry in which a negative electrode active material is dispersed in a non-aqueous electrolyte solution containing a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s.

[0079] 〔20〕

[0080] The nonaqueous electrolyte secondary battery according to

[19] , wherein:

[0081] The solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s contained in the positive electrode slurry layer and the solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s contained in the negative electrode slurry layer both contain acetonitrile.

[0082] 〔twenty one〕

[0083] The nonaqueous electrolyte secondary battery according to

[19] or

[20] , wherein:

[0084] The ratio of the solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s in the solvent in the positive electrode slurry layer is defined as X. aThe mass % of the solvent in the negative electrode slurry layer is X, and the ratio of the solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s is X. b When mass% meets X a >X b .

[0085] In the present invention and this specification, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0086] In the present invention and this specification, "nonaqueous electrolyte" refers to an electrolyte that does not contain water in fact. That is, "nonaqueous electrolyte" can contain a trace of water within the scope that does not hinder the effect of the present invention. In the present invention, the concentration of the water of "nonaqueous electrolyte" is below 200ppm (mass basis), preferably below 100ppm, more preferably below 20ppm. In addition, it is actually difficult to make the nonaqueous electrolyte completely anhydrous, and usually contains more than 1ppm of water.

[0087] In the present invention and this specification, "electrolyte" is composed of a solvent constituting the electrolyte and components dissolved in the solvent. For example, when the electrolyte further comprises an additive (solute other than the electrolyte) dissolved in the solvent on the basis of the solvent and the electrolyte dissolved in the solvent, the additive is a constituent component of the electrolyte.

[0088] Effects of the Invention

[0089] According to the manufacturing method of the non-aqueous electrolyte secondary battery of the present invention, in the battery structure in which the electrode active material layer is set as the electrode slurry layer, a non-aqueous electrolyte secondary battery with excellent output characteristics and excellent cycle characteristics can be obtained. In addition, the non-aqueous electrolyte secondary battery of the present invention has a battery structure in which the electrode active material layer is set as the electrode slurry layer, and has excellent output characteristics and excellent cycle characteristics. In addition, the slurry of the present invention is suitable for forming the electrode slurry layer of the above-mentioned non-aqueous electrolyte secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0090] Figure 1 It is a longitudinal sectional view schematically showing the basic structure of the nonaqueous electrolyte secondary battery of the present invention. DETAILED DESCRIPTION

[0091] [Method for producing non-aqueous electrolyte secondary battery]

[0092] Figure 1This is a cross-sectional view schematically showing the stacked structure of a general non-aqueous electrolyte secondary battery 10, including the working electrode when operating as a battery. The non-aqueous electrolyte secondary battery 10 has a stacked structure that includes a negative electrode collector 1, a negative electrode active material layer 2, a separator 3, a positive electrode active material layer 4, and a positive electrode collector 5 in order when viewed from the negative electrode side. The space between the negative electrode active material layer 2 and the positive electrode active material layer 4 is filled with a non-aqueous electrolyte (not shown) and is separated by a separator 3. The separator 3 has pores and, in normal battery usage, functions as a separation membrane between the positive and negative electrodes that allows the electrolyte and ions to pass through while insulating the positive and negative electrodes. With this structure, for example, in the case of a lithium-ion secondary battery, electrons (e) are supplied to the negative electrode side through an external circuit during charging. - ), at the same time, lithium ion (Li + ) moves from the positive electrode through the electrolyte and accumulates in the negative electrode. On the other hand, during discharge, the lithium ions (Li + ) returns to the positive electrode side via the electrolyte, and the electrons are supplied to the working portion 6. In the example shown in the figure, the working portion 6 is a light bulb, which is lit by discharge.

[0093] In the present invention and this specification, the negative electrode current collector 1 and the negative electrode active material layer 2 are collectively referred to as the negative electrode or negative electrode layer, the positive electrode active material layer 4 and the positive electrode current collector 5 are collectively referred to as the positive electrode or positive electrode layer, and the negative electrode and the positive electrode are collectively referred to as the electrode or electrode layer. In addition, the negative electrode active material layer 2 and the positive electrode active material layer 4 are collectively referred to as the electrode active material layer.

[0094] Next, the characteristic basic structure of the non-aqueous electrolyte secondary battery (also referred to as the "secondary battery of the present invention") obtained by the manufacturing method of the non-aqueous electrolyte secondary battery of the present invention (hereinafter, also referred to as the "manufacturing method of the present invention") is described. As described above, in the secondary battery of the present invention, the electrode active material layer is an electrode slurry layer formed by dispersing the electrode active material in the non-aqueous electrolyte. Therefore, from the point of view that the electrode active material layer is a slurry (suspension, dispersion) dispersed in the non-aqueous electrolyte, its structure is different from that of a general non-aqueous electrolyte secondary battery.

[0095] That is, in a general non-aqueous electrolyte secondary battery, a coating liquid is prepared in which an electrode active material is dispersed in a medium that does not contain an electrolyte, the coating liquid is applied to a collector to form a coating film, and the coating film is dried to form a thin film electrode active material layer. A binding material (binder) is usually added to the coating liquid to form a hard electrode active material layer firmly bonded between electrode active material particles. Since a non-aqueous electrolyte is present on the electrode active material layer thus formed (between the negative electrode active material layer and the positive electrode active material layer), the electrode active material layer is in the state of a hard solid particle layer as a whole, rather than a slurry layer, even if there is a portion in which a non-aqueous electrolyte can penetrate.

[0096] In contrast, in the secondary battery of the present invention, the electrode active material layer is an electrode slurry layer using a non-aqueous electrolyte as a medium. When the electrode slurry layer functions as an electrode active material layer, strong adhesion between the electrode active material particles is not required, so the electrode slurry layer generally does not contain a binding material. Except that the electrode active material layer is an electrode slurry layer and that the electrode slurry layer is in contact with the separator, the basic layer structure of the secondary battery of the present invention is similar to that of the present invention. Figure 1 The layer structures shown are identical.

[0097] The materials, nonaqueous electrolytes, components, etc. used in the nonaqueous electrolyte secondary battery of the present invention can be appropriately applied to materials used in conventional nonaqueous electrolyte secondary batteries, except for the composition of the solvent used in the nonaqueous electrolyte. In addition, regarding the preparation method of the nonaqueous electrolyte secondary battery of the present invention, in addition to forming the electrode active material layer into a slurry layer composed of a specific solvent, conventional methods can also be appropriately adopted. For example, Japanese Patent Publication No. 2016-201308, Japanese Patent Publication No. 2005-108835, Japanese Patent Publication No. 2012-185938, Japanese Patent Publication No. 2017-147222, etc. can be appropriately referred to.

[0098] Next, preferred embodiments of the production method of the present invention will be described.

[0099] The manufacturing method of the present invention includes the following steps (a1) to (c1) in a preferred embodiment (also referred to as "the first embodiment"). In the first embodiment, the order of performing the steps (a1) and (b1) is not limited, and the positive electrode layer component may be obtained by the step (a1) and then the negative electrode layer component may be obtained by the step (b1), or the negative electrode layer component may be obtained by the step (b1) and then the positive electrode layer component may be obtained by the step (a1), or the steps (a1) and (b1) may be performed simultaneously in parallel.

[0100] (a1) obtaining a positive electrode layer member composed of a laminate of a positive electrode current collector and a positive electrode slurry layer in which a positive electrode active material is dispersed in a non-aqueous electrolyte solution at least part of which is a solvent having a relative dielectric constant of 5 or more and a viscosity of less than 2 mPa·s;

[0101] (b1) forming a laminated structure of a negative electrode current collector and a negative electrode slurry layer in which a negative electrode active material is dispersed in a non-aqueous electrolyte solution having a relative dielectric constant of less than 5.0 and / or a viscosity of 2.0 mPa·s or more, and obtaining a negative electrode layer component consisting of a laminate of the negative electrode current collector and the negative electrode slurry layer by making the negative electrode slurry layer contain a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s; and

[0102] (c1) The positive electrode layer member, the separator, and the negative electrode layer member are stacked to form a stacked structure such that one side of the separator is in contact with the positive electrode slurry layer and the other side of the separator is in contact with the negative electrode slurry layer.

[0103] The above steps (a1) to (c1) are described in detail.

[0104] <Step (a1)>

[0105] Step (a1) is a step of obtaining a positive electrode layer member composed of a laminate of a positive electrode collector and a positive electrode slurry layer. At least a portion of the solvent of the nonaqueous electrolyte constituting the positive electrode slurry layer is a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s.

[0106] (Solvent with relative dielectric constant of 5.0 or more and viscosity of less than 2.0 mPa·s)

[0107] The solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s (also referred to as a "high dielectric constant low viscosity solvent") has a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s. The relative dielectric constant and viscosity are determined by the method described in the Examples described below.

[0108] The relative dielectric constant of the high dielectric constant low viscosity solvent constituting the positive electrode slurry layer is more preferably 6.0 or more, and further preferably 6.5 or more. In addition, the relative dielectric constant is also preferably 7.0 or more, and is also preferably 10.0 or more, and is also preferably 15.0 or more, and is also preferably 20.0 or more. In addition, the relative dielectric constant is usually 60.0 or less, preferably 50.0 or less, and is further preferably 45.0 or less, and is also preferably 40.0 or less. If the relative dielectric constant is expressed as a preferred range, it is preferably 5.0 to 60.0, more preferably 6.0 to 60.0, further preferably 6.5 to 50.0, and is also preferably 7.0 to 45.0, and is also preferably 10.0 to 45.0, and is also preferably 15.0 to 45.0, and is also preferably 20.0 to 40.0.

[0109] The viscosity of the high dielectric constant low viscosity solvent constituting the positive electrode slurry layer is preferably 1.5 mPa·s or less, more preferably 1.2 mPa·s or less, further preferably 1.0 mPa·s or less, further preferably 0.8 mPa·s or less, further preferably 0.7 mPa·s or less, further preferably 0.6 mPa·s or less, further preferably 0.5 mPa·s or less. In addition, the viscosity is usually 0.1 mPa·s or more, preferably 0.2 mPa·s or more, and further preferably 0.3 mPa·s or more. When the viscosity is expressed as a preferred range, it is preferably 0.1 mPa·s or more and less than 2.0 mPa·s, more preferably 0.2 to 1.5 mPa·s, further preferably 0.2 to 1.2 mPa·s, further preferably 0.2 to 1.0 mPa·s, further preferably 0.2 to 0.8 mPa·s, further preferably 0.3 to 0.7 mPa·s, further preferably 0.3 to 0.6 mPa·s, and particularly preferably 0.3 to 0.5 mPa·s.

[0110] As the high dielectric constant low viscosity solvent constituting the positive electrode slurry layer, it is preferred to use a compound having at least one of a cyano group, an ester bond, and an ether bond. More preferably, the high dielectric constant low viscosity solvent constituting the positive electrode slurry layer is a compound having at least one of a cyano group, an ester bond, and an ether bond.

[0111] The compound having at least one of a cyano group, an ester bond, and an ether bond, which is preferred as a high dielectric constant low viscosity solvent, is preferably a compound represented by any one of the following formulae (1) to (3).

[0112] [Chemical formula 2]

[0113]

[0114] In the above formulas, R 11 ~R 14 represents an alkyl group having 1 to 3 carbon atoms. 15represents a hydrogen atom or a fluorine atom. n is an integer from 1 to 3. In the above formula (2), the two R 12 In the above formula (3), R 13 and R 14 They can be connected to each other to form a ring.

[0115] In formula (1), as R 11 The alkyl group having 1 to 3 carbon atoms that can be used is preferably a methyl group, an ethyl group, an isopropyl group or an n-propyl group, or a group in which one or more hydrogen atoms of these groups are substituted by fluorine atoms. The alkyl group having fluorine atoms may be a perfluoroalkyl group, or a group in which a part of the hydrogen atoms of the alkyl group are substituted by fluorine atoms. The number of fluorine atoms in the alkyl group having fluorine atoms is preferably 1 to 5, more preferably 1 to 3.

[0116] In formula (2), as R 12 The alkyl group having 1 to 3 carbon atoms that can be used is preferably a methyl group or an ethyl group, or a group in which one or more hydrogen atoms of these groups are substituted with fluorine atoms. The alkyl group having fluorine atoms may be a perfluoroalkyl group, or a group in which a part of the hydrogen atoms of the alkyl group are substituted with fluorine atoms. The number of fluorine atoms in the alkyl group having fluorine atoms is preferably 1 to 5, more preferably 1 to 3.

[0117] n is preferably 1 or 2, more preferably 1.

[0118] When the two R in formula (2) 12 When connected to each other to form a ring, the number of ring members of the formed ring is preferably 5 to 10, more preferably 5 to 8, further preferably 5 or 6, further preferably 6. 12 The ring formed by connecting to each other is particularly preferably 1,4-dioxane. 15 They may be the same or different from each other, but are preferably the same.

[0119] In formula (3), as R 13 and R 14 The alkyl group having 1 to 3 carbon atoms that can be used is preferably a methyl group or an ethyl group, or a group in which one or more of the hydrogen atoms in these groups are replaced by fluorine atoms. The alkyl group having fluorine atoms may be a perfluoroalkyl group, and is also preferably a group in which a part of the hydrogen atoms in the alkyl group are replaced by fluorine atoms. The number of fluorine atoms in the alkyl group having fluorine atoms is preferably 1 to 5, more preferably 1 to 3. When R in formula (3) 13 and R 14 When they are linked to each other to form a ring, the number of ring members of the formed ring is preferably 5 to 10, more preferably 5 to 8, and even more preferably 5 or 6. 13 and R 14 The ring formed by connecting to each other is particularly preferably γ-butyrolactone or δ-valerolactone.

[0120] Preferred specific examples of the compounds represented by the above formulae (1) to (3) are shown below. In the symbols of the following compounds, Me represents a methyl group, and Et represents an ethyl group.

[0121] [Chemical formula 3]

[0122]

[0123] Among the solvents constituting the positive electrode slurry layer, one or two or more of the high dielectric constant and low viscosity solvents described above can be used.

[0124] The high dielectric constant low viscosity solvent preferably comprises acetonitrile, propionitrile or isobutyronitrile, and more preferably acetonitrile.

[0125] In addition, the high dielectric constant low viscosity solvent described in step (a1) is not limited to step (a1), but is a solvent applicable as an explanation of the high dielectric constant low viscosity solvent in all steps. That is, when referred to as "a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s" in the present invention or this specification, reference is made to the high dielectric constant low viscosity solvent described above.

[0126] (Non-aqueous electrolyte)

[0127] In step (a1), the non-aqueous electrolyte constituting the positive electrode slurry layer preferably contains the above-mentioned high dielectric constant low viscosity solvent as a solvent and further contains other solvents (solvents with a relative dielectric constant of less than 5.0 and / or a viscosity of 2.0 mPa·s or more). The above-mentioned high dielectric constant low viscosity solvent may be contained in the non-aqueous electrolyte when the slurry is applied to the collector when forming the positive electrode slurry layer, or may be contained in the slurry after the slurry is applied when forming the positive electrode slurry. The solvent and electrolyte of the non-aqueous electrolyte constituting the positive electrode slurry layer are described in sequence.

[0128] -Solvents-

[0129] In step (a1), at least a part of the solvent (same as the solvent constituting the positive electrode slurry layer) contained in the non-aqueous electrolyte constituting the positive electrode slurry layer is the above-mentioned high dielectric constant low viscosity solvent. In the positive electrode slurry layer formed in step (a1), the proportion of the above-mentioned high dielectric constant low viscosity solvent occupied in the solvent (in all solvents) is preferably 70% by mass or less, more preferably 60% by mass or less, further preferably 50% by mass or less, further preferably 40% by mass or less, further preferably 35% by mass or less, also preferably 30% by mass or less, also preferably 25% by mass or less, also preferably 20% by mass or less. And, the ratio is preferably 5% by mass or more, more preferably 8% by mass or more, further preferably 10% by mass or more, further preferably 12% by mass or more, further preferably 14% by mass or more, also preferably 16% by mass or more, also preferably 18% by mass or more. In the positive electrode slurry layer formed in step (a1), if the ratio of the high dielectric constant low viscosity solvent in the solvent is expressed as a preferred range, it is preferably 5 to 70% by mass, more preferably 8 to 60% by mass, further preferably 10 to 50% by mass, further preferably 12 to 40% by mass, further preferably 14 to 35% by mass, also preferably 16 to 30% by mass, also preferably 18 to 25% by mass, and also preferably 18 to 20% by mass. In addition, it is also preferably 5 to 60% by mass, also preferably 5 to 50% by mass, also preferably 5 to 40% by mass, also preferably 5 to 35% by mass, also preferably 5 to 30% by mass, also preferably 5 to 25% by mass, and also preferably 5 to 20% by mass.

[0130] In the positive electrode slurry layer formed in step (a1), as a solvent other than the above-mentioned high dielectric constant and low viscosity solvent (solvent with a relative dielectric constant of less than 5.0 and / or a viscosity of 2.0 mPa·s or more), a solvent commonly used in a non-aqueous electrolyte can be widely used. For example, it is preferred to use an aprotic organic solvent with a relative dielectric constant of less than 5.0 and / or a viscosity of 2.0 mPa·s or more, and the aprotic organic solvent preferably has 2 to 10 carbon atoms. As a preferred example of the above-mentioned solvent other than the high dielectric constant and low viscosity solvent, chain or cyclic carbonate compounds can be cited, and as a specific example, ethylene carbonate, dimethyl carbonate, etc. can be cited. In addition, in the present invention, vinylene carbonate is not a solvent, but is classified as an additive (film forming agent). That is, even if it is a compound that can act like a solvent, a compound that forms a film on the surface of the active material by sacrificing reaction earlier than solvents such as ethylene carbonate and dimethyl carbonate (compared with solvents such as ethylene carbonate and dimethyl carbonate, the reduction rate during initial charge and discharge is high and a film is formed on the surface of the negative electrode) is classified as an additive (film forming agent) rather than a solvent.

[0131] -Electrolytes-

[0132] The electrolyte used in the non-aqueous electrolyte is preferably a salt of a metal ion belonging to Group 1 or Group 2 of the periodic table. The salt of the metal ion to be used can be appropriately selected according to the purpose of use of the non-aqueous electrolyte. For example, lithium salts, potassium salts, sodium salts, calcium salts, magnesium salts, etc. can be cited. When used in a non-aqueous electrolyte secondary battery, etc., lithium salts are preferred from the viewpoint of output. When the non-aqueous electrolyte is used as a non-aqueous electrolyte for a lithium ion secondary battery, a lithium salt is selected as the salt of the metal ion. As a lithium salt, a lithium salt commonly used in the electrolyte of a non-aqueous electrolyte for a lithium ion secondary battery can be used. Specific examples are shown below.

[0133] (L-1) Inorganic lithium salts: inorganic fluoride salts such as LiPF6, LiBF4, LiAsF6, LiSbF6, perhalogen salts such as LiClO4, LiBrO4, LiIO4, inorganic chloride salts such as LiAlCl4, etc.

[0134] (L-2) Fluorine-containing organic lithium salts: perfluoroalkanesulfonates such as LiCF3SO3, perfluoroalkanesulfonimide salts such as LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(FSO2)2, LiN(CF3SO2)(C4F9SO2), perfluoroalkylsulfonylmethyl salts such as LiC(CF3SO2)3, perfluoroalkylsulfonylmethyl salts such as Li[PF5(CF2CF2CF3)], Li[PF4(CF2CF2CF3)2], Li[PF3(CF2CF2CF3)3], Li[PF5(CF2CF2CF2CF3)], Li[PF4(CF2CF2CF2CF3)2], Li[PF3(CF2CF2CF2CF3)3], etc.

[0135] (L-3) Oxalate borate: lithium bis(oxalate)borate, lithium difluorooxalate borate, etc.

[0136] Among these, preferred are LiPF6, LiBF4, LiAsF6, LiSbF6, LiClO4, Li(Rf1SO3), LiN(Rf1SO2)2, LiN(FSO2)2, and LiN(Rf1SO2)(Rf2SO2), and more preferred are lithium imine salts such as LiPF6, LiBF4, LiN(Rf1SO2)2, LiN(FSO2)2, and LiN(Rf1SO2)(Rf2SO2). Wherein, Rf1 and Rf2 represent perfluoroalkyl groups respectively.

[0137] The electrolyte used in the non-aqueous electrolyte solution may be used alone or in any combination of two or more.

[0138] The concentration of the electrolyte in the non-aqueous electrolyte can be appropriately selected according to the purpose of use of the non-aqueous electrolyte. In the non-aqueous electrolyte, 0.5 to 1.5 M (mol / L) is generally preferred. In addition, the concentration of the electrolyte in the non-aqueous electrolyte is preferably 0.9 M or more, more preferably 0.9 to 1.5 M, further preferably 1.0 to 1.5 M, and further preferably 1.1 to 1.4 M.

[0139] In step (a1), the ionic conductivity of the nonaqueous electrolyte constituting the positive electrode slurry layer is more preferably 8mS / cm or more, more preferably 10mS / cm or more, and more preferably 12mS / cm or more. The ionic conductivity is preferably 20mS / cm or less, more preferably 19mS / cm or less, and also preferably 18mS / cm or less. If the ionic conductivity is expressed as a preferred range, it is preferably 8 to 20mS / cm, more preferably 8 to 19mS / cm, more preferably 10 to 18mS / cm, and more preferably 12 to 18mS / cm. The ionic conductivity can be determined by the method described in the embodiments described later.

[0140] -additive-

[0141] In step (a1), the non-aqueous electrolyte constituting the positive electrode slurry layer preferably contains an additive (film forming agent, when referred to as "additive" in the following description, it refers to the film forming agent) that reacts with the surface of the negative electrode active material to form a film. This additive itself is known and can be widely used as a commonly used additive. For example, vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, etc. can be used. In the non-aqueous electrolyte constituting the positive electrode slurry layer, the content of the above-mentioned additive is preferably 1 to 30% by mass, more preferably 2 to 28% by mass, further preferably 2 to 26% by mass, further preferably 3 to 24% by mass, and further preferably 4 to 22% by mass.

[0142] (Positive electrode active material)

[0143] The positive electrode active material is preferably capable of reversibly inserting and releasing lithium ions. The material is not particularly limited as long as it has the above-mentioned properties, and may be transition metal oxides, organic matter, sulfur and other elements that can be complexed with Li, or a complex of sulfur and metal.

[0144] Among them, as the positive electrode active material, it is preferred to use a transition metal oxide, and more preferably a transition metal element M a (one or more elements selected from Co, Ni, Fe, Mn, Cu and V) transition metal oxide. In addition, the element M may be mixed in the transition metal oxide. b(Elements of Group 1 (Ia) of the periodic table, elements of Group 2 (IIa) except lithium, Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P or B, etc.) As a mixed amount, it is preferable to have 1:1 relative to the transition metal element M a The amount of (100 mol%) is 0 to 30 mol%. More preferably, the mixture is synthesized so that the molar ratio of Li / Ma becomes 0.3 to 2.2.

[0145] Specific examples of transition metal oxides include (MA) transition metal oxides having a layered rock salt structure, (MB) transition metal oxides having a spinel structure, (MC) lithium-containing transition metal phosphate compounds, (MD) lithium-containing transition metal halophosphate compounds, and (ME) lithium-containing transition metal silicate compounds.

[0146] Specific examples of transition metal oxides having a layered rock salt structure (MA) include LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), LiNi 0.85 Co 0.10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).

[0147] Specific examples of the transition metal oxide (MB) having a spinel structure include LiMn2O4 (LMO), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8 and Li2NiMn3O8.

[0148] As (MC) lithium-containing transition metal phosphate compounds, for example, there can be mentioned olivine-type iron phosphates such as LiFePO4 and Li3Fe2(PO4)3, pyrophosphates such as LiFeP2O7, cobalt phosphates such as LiCoPO4, and monoclinic NASICON-type vanadium phosphates such as Li3V2(PO4)3 (lithium vanadium phosphate).

[0149] Examples of the (MD) lithium-containing transition metal halophosphate compound include iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F.

[0150] Examples of the (ME) lithium-containing transition metal silicate compound include Li2FeSiO4, Li2MnSiO4, and Li2CoSiO4.

[0151] In the present invention, (MA) is preferably a transition metal oxide having a layered rock salt structure, and more preferably LCO or NMC.

[0152] The shape of the positive electrode active material is not particularly limited, but preferably in a particle shape. The average particle size (sphere-converted average particle size) of the positive electrode active material is not particularly limited. For example, it can be set to 0.1 to 50 μm. In order to make the positive electrode active material a predetermined particle size, a conventional pulverizer or classifier can be used. The positive electrode active material obtained by the calcination method can be used after washing with water, an acidic aqueous solution, an alkaline aqueous solution, or an organic solvent.

[0153] The above-mentioned positive electrode active materials may be used alone or in combination of two or more.

[0154] When the positive electrode active material layer is formed, the positive electrode active material layer has a unit area (cm 2 The mass (mg) (weight per unit area) of the positive electrode active material in the battery is not particularly limited and can be appropriately determined according to the designed battery capacity.

[0155] In step (a1), the content of the positive electrode active material in the positive electrode slurry layer is not particularly limited, and is preferably 20 to 70% by volume, more preferably 25 to 65% by volume, further preferably 30 to 60% by volume, and further preferably 35 to 55% by volume. In addition, the content of the positive electrode active material in the positive electrode slurry is also preferably set to 40% by volume or more, more preferably 40 to 60% by volume, and also preferably 40 to 55% by volume.

[0156] In step (a1), the method for forming the stack of the positive electrode collector and the positive electrode slurry layer (positive electrode layer component) is not particularly limited. For example, the positive electrode layer component can be obtained by coating a positive electrode slurry containing the constituent components of the positive electrode slurry layer (solvent, positive electrode active material, electrolyte, additives as needed, conductive additives, etc.) on the positive electrode collector to form a coating film of a desired thickness.

[0157] The method of applying the slurry is not particularly limited, and for example, it can be applied using a roll coater or drop coating, or the slurry can be evenly placed on the collector and then pressed (roller pressing or plate pressing), or the slurry can be placed in a frame of a specified thickness and stretched for application.

[0158] The solvent of the positive electrode slurry can be adjusted to make the formed positive electrode slurry layer contain the above-mentioned high dielectric constant low viscosity solvent of the above-mentioned desired amount. In addition, the solvent of the positive electrode slurry can also be a form of the above-mentioned high dielectric constant low viscosity solvent containing a concentration lower than the above-mentioned desired amount, or a form that does not contain a high dielectric constant low viscosity solvent. In this case, after the coating film is formed by the positive electrode slurry, the high dielectric constant low viscosity solvent is subsequently added to the coating film, and the concentration of the above-mentioned high dielectric constant low viscosity solvent in the coating film is increased to the above-mentioned desired level, so that the positive electrode slurry layer can be made.

[0159] In the positive electrode layer component obtained in step (a1), the thickness of the positive electrode slurry layer is preferably 100 μm or more, more preferably 150 μm or more, also preferably 200 μm or more, also preferably 250 μm or more, and also preferably 300 μm or more. In addition, the thickness of the positive electrode slurry layer is usually 1000 μm or less, preferably 800 μm or less, more preferably 700 μm or less, and may also be 650 μm or less. If the thickness of the positive electrode slurry layer is expressed as a preferred range, it is preferably 100 to 1000 μm, more preferably 150 to 800 μm, further preferably 200 to 700 μm, further preferably 250 to 700 μm, and particularly preferably 300 to 650 μm.

[0160] <Process (b1)>

[0161] Step (b1) is a step for obtaining a negative electrode layer component consisting of a laminate of a negative electrode current collector and a negative electrode slurry layer. Moreover, the negative electrode slurry formed by dispersing the negative electrode active material in a non-aqueous electrolyte is applied to the negative electrode current collector to form a coating, and the coating (negative electrode slurry layer) does not contain the above-mentioned high dielectric constant low viscosity solvent. That is, the solvent in the negative electrode slurry layer is a solvent having a relative dielectric constant of less than 5.0 and / or a viscosity of 2.0 mPa s or more. The relative dielectric constant is less than 5.0 and / or the viscosity is 2.0 mPa s or more as described in step (a1).

[0162] In addition, in the present invention, "the above-mentioned high dielectric constant low viscosity solvent is not included in the negative electrode slurry layer" means that the above-mentioned high dielectric constant low viscosity solvent is substantially not included in the negative electrode slurry layer. That is, within the scope of not damaging the effect of the present invention, a small amount of the above-mentioned high dielectric constant low viscosity solvent (for example, the proportion of the above-mentioned high dielectric constant low viscosity solvent in the solvent constituting the negative electrode slurry layer is 5% by mass or less, preferably 2% by mass or less, and more preferably 1% by mass or less) of the above-mentioned high dielectric constant low viscosity solvent may be included in the negative electrode slurry layer.

[0163] After forming the laminated structure of the negative electrode current collector and the negative electrode slurry layer, the above-mentioned high dielectric constant low viscosity solvent is added to the negative electrode slurry layer, thereby obtaining a negative electrode layer component consisting of a laminate of the negative electrode current collector and the negative electrode slurry layer. In addition, the high dielectric constant low viscosity solvent used in the negative electrode slurry layer may be the same as the high dielectric constant low viscosity solvent used in the positive electrode slurry layer, or it may be different, preferably the same. In the negative electrode slurry layer formed in step (b1), the proportion of the above-mentioned high dielectric constant low viscosity solvent in the solvent is preferably 70% by mass or less, more preferably 60% by mass or less, further preferably 50% by mass or less, further preferably 40% by mass or less, further preferably 35% by mass or less, also preferably 30% by mass or less, also preferably 25% by mass or less, and also preferably 20% by mass or less. In addition, the ratio is preferably 5% by mass or more, more preferably 8% by mass or more, further preferably 10% by mass or more, further preferably 12% by mass or more, further preferably 14% by mass or more, also preferably 16% by mass or more, and also preferably 18% by mass or more. In the negative electrode slurry layer formed in step (b1), if the ratio of the high dielectric constant low viscosity solvent in the solvent is expressed as a preferred range, it is preferably 5-70% by mass, more preferably 8-60% by mass, further preferably 10-50% by mass, further preferably 12-40% by mass, further preferably 14-35% by mass, also preferably 16-30% by mass, also preferably 18-30% by mass, also preferably 18-25% by mass, and also preferably 18-20% by mass. In addition, it is also preferably 5-60% by mass, also preferably 5-50% by mass, also preferably 5-40% by mass, also preferably 5-35% by mass, also preferably 5-30% by mass, also preferably 5-25% by mass, and also preferably 5-20% by mass.

[0164] The ratio (P A mass %) and the ratio (Q A Mass %) can be the same or different. Preferably 0.5Q A ≤P A ≤2Q A , more preferably 0.7Q A ≤P A ≤2Q A , and more preferably 0.8Q A ≤P A ≤1.5Q A , and more preferably 0.8Q A ≤P A ≤1.3Q A, and more preferably 0.9Q A ≤P A ≤1.2Q A .

[0165] The high dielectric constant low viscosity solvent used in the negative electrode slurry layer preferably comprises acetonitrile, propionitrile or isobutyronitrile, preferably acetonitrile.

[0166] In step (b1), the preferred form of the electrolyte contained in the nonaqueous electrolyte constituting the negative electrode slurry layer is the same as the preferred form of the electrolyte contained in the nonaqueous electrolyte constituting the positive electrode slurry layer described above. The electrolyte contained in the nonaqueous electrolyte constituting the positive electrode slurry layer in step (a1) and the electrolyte contained in the nonaqueous electrolyte constituting the negative electrode slurry layer in step (b1) are preferably the same compound.

[0167] Furthermore, in step (b1), the content of the electrolyte in the non-aqueous electrolyte constituting the negative electrode slurry layer is preferably 0.5 to 1.5 M (mol / L). Furthermore, the concentration of the electrolyte in the non-aqueous electrolyte is preferably 0.9 M or more, more preferably 0.9 to 1.5 M, further preferably 1.0 to 1.5 M, and further preferably 1.1 to 1.4 M.

[0168] In step (b1), the ionic conductivity of the non-aqueous electrolyte constituting the negative electrode slurry layer is more preferably 8 mS / cm or more, more preferably 10 mS / cm or more, and more preferably 12 mS / cm or more. The ionic conductivity is preferably 20 mS / cm or less, more preferably 19 mS / cm or less, and also preferably 18 mS / cm or less. If the ionic conductivity is expressed as a preferred range, it is preferably 8 to 20 mS / cm, more preferably 8 to 19 mS / cm, more preferably 10 to 18 mS / cm, and more preferably 12 to 18 mS / cm.

[0169] In step (b1), the non-aqueous electrolyte constituting the negative electrode slurry layer preferably contains the above-mentioned additive that reacts with the surface of the negative electrode active material to form a film. In the non-aqueous electrolyte constituting the negative electrode slurry layer, the content of the above-mentioned additive is preferably 1 to 30% by mass, more preferably 2 to 28% by mass, further preferably 2 to 26% by mass, further preferably 3 to 24% by mass, and further preferably 4 to 22% by mass.

[0170] (Negative electrode active material)

[0171] The negative electrode active material is preferably capable of reversibly entrapping and releasing lithium ions. The material is not particularly limited as long as it has the above-mentioned characteristics, and carbonaceous materials, silicon-based materials, metal oxides, metal composite oxides, lithium monomers, lithium alloys, or negative electrode active materials capable of forming alloys with lithium can be cited. Among them, from the viewpoint of reliability, carbonaceous materials or silicon-based materials can be preferably used.

[0172] The carbonaceous material used as the negative electrode active material refers to a material substantially composed of carbon. For example, carbonaceous materials obtained by calcining various synthetic resins such as carbon black such as petroleum pitch, graphite (natural graphite, artificial graphite such as vapor-grown graphite, etc.), and PAN (polyacrylonitrile) resins or furfuryl alcohol resins can be cited. In addition, various carbon fiber types such as PAN-based carbon fiber, cellulose-based carbon fiber, pitch-based carbon fiber, vapor-grown carbon fiber, dehydrated PVA (polyvinyl alcohol)-based carbon fiber, lignin carbon fiber, glassy carbon fiber, and activated carbon fiber, mesophase microspheres, graphite whiskers, and flat graphite can also be cited.

[0173] The metal oxide and metal composite oxide applicable as the negative electrode active material are not particularly limited as long as they are oxides capable of occluding and releasing lithium, and are preferably amorphous oxides, and chalcogenides which are reaction products of metal elements and elements of Group 16 of the periodic table may also be preferably mentioned. The amorphous material referred to herein refers to a material having a broad scattering band having a vertex in the region of 20° to 40° in terms of 2θ value in an X-ray diffraction method using CuKα rays, and may also have crystalline diffraction lines.

[0174] Among the compound group including the above-mentioned amorphous oxides and chalcogenides, amorphous oxides of semimetallic elements and the above-mentioned chalcogenides are more preferred, and oxides or chalcogenides composed of elements of Groups 13 (IIIB) to 15 (VB) of the periodic table, Al, Ga, Si, Sn, Ge, Pb, Sb and Bi, alone or in combination of two or more thereof, are particularly preferred. Specific examples of preferred amorphous oxides and chalcogenides include Ga2O3, GeO, PbO, PbO2, Pb2O3, Pb2O4, Pb3O4, Sb2O3, Sb2O4, Sb2O8Bi2O3, Sb2O8Si2O3, Sb2O5, Bi2O3, Bi2O4, GeS, PbS, PbS2, Sb2S3 and Sb2S5.

[0175] From the viewpoint of high current density charge and discharge characteristics, the metal (composite) oxide and the above-mentioned chalcogenide preferably contain at least one of titanium and lithium as a constituent component. As the metal composite oxide containing lithium (lithium composite metal oxide), for example, a composite oxide of lithium oxide and the above-mentioned metal (composite) oxide or the above-mentioned chalcogenide can be cited, and more specifically, Li2SnO2 can be cited.

[0176] The negative electrode active material also preferably contains titanium atoms. More specifically, due to TiNb2O7 (titanium niobium oxide [NTO]), Li4Ti5O 12(Lithium titanate [LTO]) has a small volume change when lithium ions are stored and released, and is therefore preferred from the viewpoint of excellent rapid charge and discharge characteristics, suppressing electrode degradation, and being able to extend the life of the lithium ion secondary battery.

[0177] The lithium alloy used as the negative electrode active material is not particularly limited as long as it is an alloy commonly used as a negative electrode active material for secondary batteries, and examples thereof include lithium aluminum alloys.

[0178] The negative electrode active material that can form an alloy with lithium is not particularly limited as long as it is usually used as the negative electrode active material of the secondary battery. This active material has large expansion and contraction caused by charging and discharging. As mentioned above, the adhesion of the solid particles is reduced, but in the present invention, high adhesion can be achieved by the above-mentioned binder. As such an active material, negative electrode active materials having silicon atoms or tin atoms, metals such as Al and In can be cited. Preferably, a negative electrode active material having silicon atoms (active materials containing silicon atoms) that can achieve a higher battery capacity is used, and more preferably, an active material containing silicon atoms having a silicon atom content of more than 40 mol% of all constituent atoms.

[0179] Generally speaking, compared with carbon negative electrodes (graphite and acetylene black, etc.), negative electrodes containing these negative electrode active materials (for example, Si negative electrodes containing active materials containing silicon atoms, Sn negative electrodes containing active materials having tin atoms) can contain more Li ions. That is, the amount of Li ions contained per unit mass increases. Therefore, the battery capacity (energy density) can be increased. As a result, it has the advantage of being able to extend the battery driving time.

[0180] As active materials containing silicon atoms, for example, silicon materials such as Si and SiOx (0<x≤1), alloys containing titanium, vanadium, chromium, manganese, nickel, copper or lanthanum (for example, LaSi2, VSi2) or organized active materials (for example, LaSi2 / Si), and active materials containing silicon atoms and tin atoms such as SnSiO3 and SnSiS3 can be cited. In addition, SiOx itself can be used as a negative electrode active material (semi-metallic oxide), and Si is generated by the operation of the battery, so it can be used as an active material (its precursor material) that can be alloyed with lithium.

[0181] Examples of negative electrode active materials having tin atoms include Sn, SnO, SnO2, SnS, SnS2, and the above-mentioned active materials containing silicon atoms and tin atoms, etc. Furthermore, composite oxides with lithium oxide such as Li2SnO2 are also included.

[0182] The shape of the negative electrode active material is not particularly limited, but is preferably in a particulate form. The average particle size of the negative electrode active material is preferably 0.1 to 60 μm. In order to make it into a specified particle size, a conventional pulverizer or classifier is used. For example, a mortar, a ball mill, a sand mill, a vibrating ball mill, a satellite ball mill, a planetary ball mill, a rotary airflow type jet mill or a sieve can be preferably used. During pulverization, wet pulverization in which an organic solvent such as water or methanol coexists can also be performed. In order to make it into the desired particle size, classification is preferably performed. There is no particular limitation on the classification method, and a sieve, a wind classifier, etc. can be used as desired. Classification can use both dry and wet methods.

[0183] The above-mentioned negative electrode active material can be used alone or in combination of two or more. Among them, the combination of active material containing silicon atoms and carbonaceous material is preferred, and the combination of SiOx (0<x≤1) and graphite is particularly preferred. The mass ratio (SiOx / graphite) when combining SiOx (0<x≤1) and graphite is preferably less than 2, more preferably less than 1, and further preferably less than 0.5.

[0184] When the negative electrode active material layer is formed, the negative electrode active material layer has a unit area (cm 2 The mass (mg) (weight per unit area) of the negative electrode active material in the battery is not particularly limited and can be appropriately determined according to the designed battery capacity.

[0185] In step (b1), the content of the negative electrode active material in the negative electrode slurry is not particularly limited, and is preferably 20 to 70% by volume, more preferably 25 to 65% by volume, further preferably 30 to 60% by volume, further preferably 30 to 55% by volume, and particularly preferably 35 to 50% by volume. In addition, the content of the negative electrode active material in the negative electrode slurry is also preferably set to 40% by volume or more, more preferably 40 to 60% by volume, and also preferably 40 to 55% by volume.

[0186] The chemical formula of the compound obtained by the calcination method can be calculated by inductively coupled plasma (ICP) emission spectrometry as a measurement method, or can be calculated from the mass difference of the powder before and after calcination as a simple method.

[0187] In step (b1), the method for forming the stack of the negative electrode collector and the negative electrode slurry layer (negative electrode layer member) is not particularly limited and can be appropriately formed according to the method for forming the stack of the positive electrode collector and the positive electrode slurry layer (positive electrode layer member) described in step (a1).

[0188] In the negative electrode layer component obtained in step (b1), the thickness of the negative electrode slurry layer is preferably 100 μm or more, more preferably 150 μm or more, also preferably 200 μm or more, also preferably 250 μm or more, and also preferably 300 μm or more. In addition, the thickness of the negative electrode slurry layer is usually 1000 μm or less, preferably 800 μm or less, more preferably 700 μm or less, and may also be 650 μm or less. If the thickness of the negative electrode slurry layer is expressed as a preferred range, it is preferably 100 to 1000 μm, more preferably 150 to 800 μm, further preferably 200 to 700 μm, further preferably 250 to 700 μm, and particularly preferably 300 to 650 μm.

[0189] The positive electrode slurry layer in step (a1) and / or the negative electrode slurry layer in step (b1) preferably contain a conductive additive. More preferably, both the positive electrode slurry layer in step (a1) and the negative electrode slurry layer in step (b1) contain a conductive additive.

[0190] (Conductive additive)

[0191] There are no particular restrictions on the conductive aid, and a conductive aid known as a general conductive aid can be used. For example, it can be graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, Ketjen black, and furnace black, amorphous carbon such as needle coke, carbon fibers such as vapor-grown carbon fibers or carbon nanotubes, carbonaceous materials such as graphene or fullerene, or metal powders and metal fibers such as copper and nickel, or conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, and polyphenylene derivatives.

[0192] When a positive electrode active material and a conductive aid are used together, a conductive aid that does not embed and release Li and does not function as an active material when the battery is charged and discharged is used as a conductive aid. Therefore, among conductive aids, conductive aids that can function as an active material in the active material layer when the battery is charged and discharged are classified as active materials, not conductive aids. Whether or not a conductive aid functions as an active material when the battery is charged and discharged is not determined uniquely, but is determined by the combination with the active material.

[0193] The conductive auxiliary agent may be used alone or in combination of two or more.

[0194] The content of the conductive additive in the positive electrode slurry layer and the content in the negative electrode slurry layer are preferably 0.5 to 5% by volume, and more preferably 1 to 3% by volume.

[0195] The shape of the conductive aid is not particularly limited, but is preferably a particle shape. The median particle size D50 (volume basis) of the conductive aid is not particularly limited, but is, for example, preferably 0.01 to 50 μm, and more preferably 0.02 to 10.0 μm.

[0196] <Step (c1)>

[0197] In step (c1), the positive electrode layer component obtained in step (a1) and the negative electrode layer component obtained in step (b1) are stacked in such a manner that one side of the separator contacts the positive electrode slurry layer of the positive electrode layer component and the other side of the separator contacts the negative electrode slurry layer of the negative electrode layer component to form a stacked structure. Thus, a stacked body having a positive electrode collector, a positive electrode active material layer, a separator, a negative electrode active material layer and a negative electrode collector in this order can be obtained. After the tabs are set on the positive electrode collector and the negative electrode collector by a conventional method, they are sealed, thereby obtaining a laminated structure as shown in FIG. Figure 1 The non-aqueous electrolyte secondary battery shown.

[0198] In step (c1), by stacking the positive electrode layer components, the separator and the negative electrode layer components as described above, the non-aqueous electrolyte of the positive electrode slurry layer and the non-aqueous electrolyte of the negative electrode slurry layer also depend on the type of the separator, but the solvent is usually diffused and homogenized through the separator. In addition, in a non-aqueous electrolyte secondary battery that has been repeatedly charged and discharged, as a separator, for example, even if a separator formed by a polymer electrolyte in which the solvent is not easy to move is used, the solvent composition of the non-aqueous electrolyte of the positive electrode slurry layer and the non-aqueous electrolyte of the negative electrode slurry layer will usually become a roughly uniform state. That is, in the first embodiment, in order to make the obtained secondary battery show the desired effect, the following becomes its characteristic technical requirements: forming a negative electrode slurry layer as a layer in the front stage of the negative electrode slurry layer (a layer in which the solvent of the non-aqueous electrolyte is a solvent with a relative dielectric constant less than 5.0 and / or a viscosity of 2.0 mPa·s or more), and then, making the negative electrode slurry layer subsequently contain (later added) a high dielectric constant low viscosity solvent.

[0199] Next, another preferred embodiment of the manufacturing method of the present invention (also referred to as "the second embodiment") is described. The second embodiment includes the following steps (a2) to (c2). In the second embodiment, the order of performing the steps (a2) and (b2) is not limited. The positive electrode layer component may be obtained by the step (a2) and then the negative electrode layer component may be obtained by the step (b2). The negative electrode layer component may be obtained by the step (b2) and then the positive electrode layer component may be obtained by the step (a2). The steps (a2) and (b2) may be performed simultaneously in parallel.

[0200] (a2) obtaining a positive electrode layer member composed of a laminate of a positive electrode current collector and a positive electrode slurry layer in which a positive electrode active material is dispersed in a non-aqueous electrolyte solution having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s at a ratio of X mass % of a solvent in the solvent;

[0201] (b2) obtaining a negative electrode layer member composed of a negative electrode current collector and a negative electrode slurry layer formed by dispersing a negative electrode active material in a non-aqueous electrolyte solution in which the ratio of a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s in the solvent is less than the above X mass %; and

[0202] (c2) The positive electrode layer member, the separator, and the negative electrode layer member are stacked to form a stacked structure such that one side of the separator is in contact with the positive electrode slurry layer and the other side of the separator is in contact with the negative electrode slurry layer.

[0203] <Step (a2)>

[0204] Step (a2) is a step of obtaining a positive electrode layer component consisting of a laminate of a positive electrode current collector and a positive electrode slurry layer. Furthermore, it is characterized in that at least a portion of the solvent of the non-aqueous electrolyte constituting the positive electrode slurry layer is the above-mentioned high dielectric constant low viscosity solvent, and the proportion (X mass %) of the above-mentioned high dielectric constant low viscosity solvent in the solvent of the non-aqueous electrolyte constituting the positive electrode slurry layer is higher than the proportion of the above-mentioned high dielectric constant low viscosity solvent in the solvent of the non-aqueous electrolyte constituting the negative electrode slurry layer in step (b2).

[0205] In the positive electrode slurry layer formed in step (a2), the proportion of the above-mentioned high dielectric constant low viscosity solvent in the solvent is preferably 70% by mass or less, more preferably 60% by mass or less, further preferably 50% by mass or less, further preferably 40% by mass or less, further preferably 35% by mass or less, also preferably 30% by mass or less, also preferably 25% by mass or less, also preferably 20% by mass or less. And, the ratio is preferably 5% by mass or more, more preferably 8% by mass or more, further preferably 10% by mass or more, further preferably 12% by mass or more, further preferably 14% by mass or more, also preferably 16% by mass or more, also preferably 18% by mass or more. In the positive electrode slurry layer formed in step (a2), if the ratio of the high dielectric constant low viscosity solvent in the solvent is expressed as a preferred range, it is preferably 5 to 70 mass %, more preferably 8 to 60 mass %, further preferably 10 to 50 mass %, further preferably 12 to 40 mass %, further preferably 14 to 35 mass %, also preferably 16 to 30 mass %, also preferably 18 to 25 mass %, also preferably 18 to 20 mass %. In addition, it is also preferably 5 to 60 mass %, also preferably 5 to 50 mass %, also preferably 5 to 40 mass %, also preferably 5 to 35 mass %, also preferably 5 to 30 mass %, also preferably 5 to 25 mass %, also preferably 5 to 20 mass %. The solvent other than the high dielectric constant low viscosity solvent constituting the positive electrode slurry layer can be applied to the solvent described in step (a1) of the first embodiment.

[0206] In the positive electrode slurry layer formed in step (a2), about the adjustment of the ratio of the above-mentioned high dielectric constant low viscosity solvent, when the positive electrode slurry containing the constituent components (solvent, positive electrode active material, electrolyte, additives as needed, conductive additives, etc.) of the positive electrode slurry layer is applied to the positive electrode collector, it can be adjusted to include the above-mentioned high dielectric constant low viscosity solvent of the above-mentioned desired amount in the positive electrode slurry. In addition, the solvent of the positive electrode slurry can also be a form of the above-mentioned high dielectric constant low viscosity solvent containing a concentration lower than the above-mentioned desired amount, or a form that does not contain a high dielectric constant low viscosity solvent. In this case, after the coating is formed by the positive electrode slurry, the high dielectric constant low viscosity solvent is subsequently added to the coating, and the concentration of the above-mentioned high dielectric constant low viscosity solvent in the coating is increased to the desired level, so that the positive electrode slurry layer can be made.

[0207] Among the solvents constituting the positive electrode slurry layer, one or two or more of the high dielectric constant and low viscosity solvents described above can be used.

[0208] The high dielectric constant low viscosity solvent preferably comprises acetonitrile, propionitrile or isobutyronitrile, and more preferably acetonitrile.

[0209] In the positive electrode slurry layer of step (a2), the description of the type or content of the positive electrode active material, electrolyte, additive and conductive auxiliary agent and the description of the ionic conductivity of the non-aqueous electrolyte can directly apply the description of the type or content of the positive electrode active material, electrolyte, additive and conductive auxiliary agent in the first embodiment. In addition, the preferred thickness of the positive electrode slurry layer in step (a2) is also the same as the preferred thickness of the positive electrode slurry layer described in the first embodiment.

[0210] <Step (b2)>

[0211] Step (b2) is a step of obtaining a negative electrode layer member composed of a laminate of a negative electrode current collector and a negative electrode slurry layer. In forming the negative electrode slurry layer, the ratio of the high dielectric constant low viscosity solvent in the solvent is set to a concentration lower than that in the positive electrode slurry layer.

[0212] In the negative electrode slurry layer formed in step (b2), the proportion of the above-mentioned high dielectric constant low viscosity solvent in the solvent is preferably less than 20% by mass, more preferably less than 15% by mass, further preferably less than 12% by mass, further preferably less than 10% by mass, further preferably less than 8% by mass, also preferably less than 7% by mass, and also preferably less than 5% by mass. In addition, the ratio is also preferably 0% by mass (excluding the above-mentioned high dielectric constant low viscosity solvent). The solvent other than the above-mentioned high dielectric constant low viscosity solvent constituting the negative electrode slurry layer can be applied to the solvent described in step (a1) of the first embodiment.

[0213] When the solvent of the negative electrode slurry layer in step (b2) contains a high dielectric constant low viscosity solvent, the ratio (P B mass %) and the ratio (Q B The relationship of mass %) is preferably 1.2Q B ≤P B , preferably 1.5Q B ≤P B , further preferably 2Q B ≤P B , and more preferably 2.5Q B ≤P B , further preferably 3Q B ≤P B , and more preferably 3.5Q B ≤P B .

[0214] In the negative electrode slurry layer of step (b2), the description of the type or content of the negative electrode active material, electrolyte, additive and conductive auxiliary agent, etc., is that the ratio of the high dielectric constant low viscosity solvent in the solvent is set to a concentration lower than that in the positive electrode slurry layer, and other than this, the description of the type or content of the negative electrode active material, electrolyte, additive and conductive auxiliary agent in the first embodiment can be directly applied. In addition, the preferred thickness of the negative electrode slurry layer in step (b2) is also the same as the preferred thickness of the negative electrode slurry layer described in the first embodiment.

[0215] In step (b2), the ionic conductivity of the nonaqueous electrolyte constituting the negative electrode slurry layer is preferably 12mS / cm or less, more preferably 11mS / cm or less, further preferably 10mS / cm or less, and further preferably 9.5mS / cm or less. The ionic conductivity is preferably 5mS / cm or more, more preferably 6mS / cm or more, and further preferably 7mS / cm or more. If the ionic conductivity is expressed as a preferred range, it is preferably 5 to 12mS / cm, more preferably 6 to 11mS / cm, further preferably 7 to 10mS / cm, and further preferably 7 to 9.5mS / cm. In addition, after the step (c2) described later, the negative electrode slurry layer is subsequently made to contain a high dielectric constant low viscosity solvent or the high dielectric constant low viscosity solvent is subsequently further concentrated, and the preferred ionic conductivity of the nonaqueous electrolyte constituting the negative electrode slurry layer is the same as the preferred ionic conductivity of the negative electrode slurry layer described in the first embodiment.

[0216] <Step (c2)>

[0217] In step (c2), the positive electrode layer component obtained in step (a2) and the negative electrode layer component obtained in step (b2) are stacked in such a manner that one side of the separator contacts the positive electrode slurry layer of the positive electrode layer component and the other side of the separator contacts the negative electrode slurry layer of the negative electrode layer component to form a stacked structure. Thus, a stacked body having a positive electrode collector, a positive electrode active material layer, a separator, a negative electrode active material layer and a negative electrode collector in this order can be obtained. After the tabs are set on the positive electrode collector and the negative electrode collector by a conventional method, they are sealed, thereby obtaining a laminated structure as shown in FIG. Figure 1 The non-aqueous electrolyte secondary battery shown.

[0218] In step (c2), by stacking the positive electrode layer components, the separator and the negative electrode layer components as described above, the non-aqueous electrolyte of the positive electrode slurry layer and the non-aqueous electrolyte of the negative electrode slurry layer are usually diffused and homogenized through the separator. That is, in the second embodiment, in order to make the obtained secondary battery show the desired effect, the following becomes its characteristic technical requirements: forming a negative electrode slurry layer that does not contain the above-mentioned high dielectric constant low viscosity solvent or contains the above-mentioned high dielectric constant low viscosity solvent at the above-mentioned low concentration, and then, through step (c2), the negative electrode slurry layer is subsequently made to contain a high dielectric constant low viscosity solvent or the high dielectric constant low viscosity solvent is subsequently further concentrated.

[0219] In any of the first embodiment and the second embodiment, it is preferable that the high dielectric constant and low viscosity solvents used are of the same type.

[0220] Furthermore, in any of the above-mentioned first embodiment and the second embodiment, preferably, in the non-aqueous electrolytic secondary battery obtained, the positive electrode slurry layer and the negative electrode slurry layer both contain acetonitrile. When acetonitrile is included in the positive electrode slurry layer, even if acetonitrile is not included in the negative electrode slurry layer just after the battery is made, the solvent will diffuse over time or repeatedly charge and discharge, thereby also including acetonitrile in the negative electrode. In addition, this diffusion is not limited to acetonitrile, and is applicable to all high dielectric constant low viscosity solvents.

[0221] In the first embodiment, after step (c1), in the second embodiment, after step (c2), it is preferred to perform CV (Constant Voltage) charging at a potential higher than the reduction potential of the high dielectric constant low viscosity solvent contained in the electrode slurry layer. By performing CV charging at such a potential, it is possible to prevent the high dielectric constant low viscosity solvent from being reduced and forming a film on the surface of the negative electrode active material, thereby reducing the battery performance or destroying the active material, and a non-aqueous electrolyte secondary battery with higher performance can be obtained.

[0222] The reduction potential can be determined by the following measurement method.

[0223] In the manufacturing method of the present invention, it is preferred that the following: when an additive (film forming agent) is added to the electrode slurry layer, the non-aqueous electrolyte secondary battery obtained will have the above-mentioned additive remaining in the electrode slurry (at least in the negative electrode slurry) even if it is repeatedly charged and discharged (for example, even if 100 cycles of charge and discharge are performed). The additive is usually consumed in the film formation on the surface of the negative electrode active material by charge and discharge. However, if the manufacturing method of the present invention is adopted, there is a tendency that a certain amount of the above-mentioned additive will remain in the electrolyte even if charge and discharge are repeated. As such an additive, vinylene carbonate is preferred. The additive concentration in the negative electrode slurry layer after repeated charge and discharge (for example, after 100 cycles of charge and discharge) is preferably 0.2% by mass or more, more preferably 0.5% by mass or more, and further preferably 0.8% by mass or more. The additive concentration also depends on the amount of the additive added to the slurry, which is usually 30% by mass or less, preferably 25% by mass or less, more preferably 20% by mass or less, and particularly preferably 15% by mass or less.

[0224] In the manufacturing method of the present invention, when the electrode slurry layer contains ethylene carbonate as a solvent, if the obtained nonaqueous electrolyte secondary battery is repeatedly charged and discharged (for example, if 100 cycles of charge and discharge are performed), in the solvent of the electrode slurry (at least in the solvent of the negative electrode slurry), when the concentration before charging and discharging is converted to 100% by mass, the concentration of ethylene carbonate is preferably reduced to less than 95% by mass. That is, if the manufacturing method of the present invention is adopted, there is a tendency that ethylene carbonate will also be efficiently consumed in the film formation of the negative electrode active material.

[0225] (Other ingredients)

[0226] In the production method of the present invention, the electrode slurry layer may contain an ionic liquid, a thickener, a defoaming agent, a leveling agent, a dehydrating agent, an antioxidant, and the like as desired.

[0227] Regarding the production method of the present invention described above, the present invention provides a slurry for a non-aqueous electrolyte secondary battery (hereinafter, also referred to as the slurry of the present invention) shown below.

[0228] [Slurry for non-aqueous electrolyte secondary batteries]

[0229] A slurry for a non-aqueous electrolyte secondary battery comprises: a non-aqueous electrolyte containing a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s; and an electrode active material.

[0230] The slurry of the present invention is a slurry suitable for forming an electrode slurry layer of a non-aqueous electrolyte secondary battery.

[0231] That is, the slurry of the present invention is suitable for forming a positive electrode slurry layer of a positive electrode layer component in the first embodiment of the manufacturing method of the present invention, or forming a positive electrode slurry layer of a positive electrode layer component in the second embodiment of the manufacturing method of the present invention, or forming a negative electrode slurry layer of a negative electrode layer component in the second embodiment of the manufacturing method of the present invention. Therefore, the composition of the slurry of the present invention and the content of each component can be directly applied to the description of the composition and content of each component of the positive electrode slurry layer of the positive electrode layer component in the first embodiment of the manufacturing method of the present invention, the positive electrode slurry layer of the positive electrode layer component in the second embodiment, or the negative electrode slurry layer of the negative electrode layer component in the second embodiment. Below, a more preferred embodiment of the slurry of the present invention is described.

[0232] In the slurry of the present invention, when the electrode active material is a positive electrode active material, the proportion of the above-mentioned high dielectric constant low viscosity solvent in the solvent is preferably 70% by mass or less, more preferably 60% by mass or less, further preferably 50% by mass or less, further preferably 40% by mass or less, further preferably 35% by mass or less, also preferably 30% by mass or less, also preferably 25% by mass or less, also preferably 20% by mass or less. In addition, the ratio is preferably 5% by mass or more, more preferably 8% by mass or more, further preferably 10% by mass or more, further preferably 12% by mass or more, further preferably 14% by mass or more, also preferably 16% by mass or more, and also preferably 18% by mass or more. If the ratio is expressed as a preferred range, it is preferably 5 to 70% by mass, more preferably 8 to 60% by mass, further preferably 10 to 50% by mass, further preferably 12 to 40% by mass, further preferably 14 to 35% by mass, also preferably 16 to 30% by mass, also preferably 18 to 25% by mass, and also preferably 18 to 20% by mass. Furthermore, it is preferably 5 to 60 mass %, preferably 5 to 50 mass %, preferably 5 to 40 mass %, preferably 5 to 35 mass %, preferably 5 to 30 mass %, preferably 5 to 25 mass %, and preferably 5 to 20 mass %.

[0233] Furthermore, in the slurry of the present invention, when the electrode active material is a negative electrode active material, the proportion of the high dielectric constant low viscosity solvent in the solvent is preferably less than 20% by mass, more preferably 15% by mass or less, further preferably 12% by mass or less, further preferably 10% by mass or less, further preferably 8% by mass or less, also preferably 7% by mass or less, also preferably 5% by mass or less, also preferably 3% by mass or less, also preferably 2% by mass or less, also preferably 1% by mass or less. When the electrode active material in the slurry of the present invention is a negative electrode active material, the proportion of the high dielectric constant low viscosity solvent in the solvent is usually 0.1% by mass or more, and can also be 0.5% by mass or more. Therefore, in the slurry of the present invention, when the electrode active material is a negative electrode active material, the proportion of the high dielectric constant low viscosity solvent in the solvent is preferably 0.1% by mass or more and less than 20% by mass, more preferably 0.1 to 15% by mass, further preferably 0.1 to 12% by mass, further preferably 0.1 to 10% by mass, also preferably 0.1 to 5% by mass, also preferably 0.1 to 3% by mass, also preferably 0.1 to 2% by mass, and also preferably 0.5 to 2% by mass.

[0234] In the slurry of the present invention, the content of the above-mentioned electrode active material in the slurry is preferably 20 to 70 volume %, more preferably 25 to 65 volume %, further preferably 30 to 60 volume %, further preferably 30 to 55 volume %, and particularly preferably 35 to 50 volume %. In addition, the content of the negative electrode active material in the negative electrode slurry is also preferably set to 40 volume % or more, more preferably 40 to 60 volume %, and also preferably 40 to 55 volume %.

[0235] The slurry of the present invention preferably contains the above-mentioned conductive auxiliary agent. In the slurry of the present invention, the content of the conductive auxiliary agent is preferably 0.5 to 5% by volume, more preferably 1 to 3% by volume.

[0236] The slurry of the present invention preferably contains acetonitrile, propionitrile or isobutyronitrile as the high dielectric constant low viscosity solvent, and it is also preferred that the high dielectric constant low viscosity solvent is acetonitrile.

[0237] Furthermore, regarding the production method or slurry of the present invention described above, the present invention provides the following nonaqueous electrolyte secondary battery.

[0238] [Non-aqueous electrolyte secondary battery]

[0239] A non-aqueous electrolyte secondary battery comprises a positive electrode slurry layer, a separator and a negative electrode slurry layer in sequence, wherein:

[0240] The positive electrode slurry layer is composed of a slurry in which a positive electrode active material is dispersed in a non-aqueous electrolyte solution containing a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s.

[0241] The negative electrode slurry layer is composed of a slurry in which a negative electrode active material is dispersed in a non-aqueous electrolyte solution containing a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s.

[0242] In the above-mentioned nonaqueous electrolyte secondary battery, the above-mentioned positive electrode slurry layer is preferably sandwiched by the positive electrode collector and the above-mentioned separator. In addition, the above-mentioned negative electrode slurry layer is preferably sandwiched by the negative electrode collector and the above-mentioned separator. That is, it is preferred that the positive electrode layer is composed of a laminate of the positive electrode collector and the positive electrode slurry layer, and the negative electrode layer is composed of a laminate of the negative electrode collector and the negative electrode slurry layer.

[0243] The description of the components of the nonaqueous electrolyte secondary battery described above can be directly applied to the embodiments described in the production method of the present invention.

[0244] In the nonaqueous electrolyte secondary battery, the high dielectric constant low viscosity solvent contained in the positive electrode slurry layer and the high dielectric constant low viscosity solvent contained in the negative electrode slurry layer preferably both contain acetonitrile, propionitrile or isobutyronitrile, more preferably acetonitrile.

[0245] In the non-aqueous electrolyte secondary battery, the ratio of the high dielectric constant low viscosity solvent in the solvent in the positive electrode slurry layer is X. a The mass % is X, and the ratio of the high dielectric constant low viscosity solvent in the solvent in the negative electrode slurry layer is X. b When the mass% is X a >X b .

[0246] <Applications of non-aqueous electrolyte secondary batteries>

[0247] The above-mentioned non-aqueous electrolyte secondary battery can be applicable to various purposes. For example, when it is carried on electronic equipment, a notebook computer, a pen input computer, a mobile computer, an e-book reader, a mobile phone, a wireless telephone handset, a pager, a handheld terminal, a portable fax machine, a portable copier, a portable printer, a stereo headset, a camcorder, a liquid crystal television, a portable vacuum cleaner, a portable CD, a small disk, an electric shaver, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, etc. can be cited. As other civilian products, automobiles, electric cars, motors, lighting equipment, toys, game consoles, load regulators, clocks, flashlights, cameras and medical equipment (pacemakers, hearing aids and shoulder massagers, etc.) can be cited. Moreover, it can be used as various military products and aviation products. And, it can also be combined with solar cells.

[0248] Among them, it is preferably suitable for applications requiring high capacity and high rate discharge characteristics. For example, in the case of large-capacity power storage devices in the future, high safety is necessary, and thus battery performance compatibility is required. In addition, electric vehicles and the like can be conceived to be equipped with high-capacity secondary batteries and charged every day at home. According to the present invention, it is possible to appropriately correspond to such a usage form and exert its excellent effect.

[0249] Example

[0250] The present invention will be described in further detail based on examples, but the present invention is not limited to these embodiments.

[0251] The abbreviations used in the following examples are as follows.

[0252] EC: Ethylene carbonate

[0253] DMC: dimethyl carbonate

[0254] VC: Vinyl carbonate

[0255] KB: Ketchen Black

[0256] PE: Polyethylene

[0257] The relative dielectric constant, viscosity, and reduction potential of the solvents used in the following examples were measured by the following methods. The results are shown in the following table.

[0258] [Measurement method of relative dielectric constant]

[0259] As the sample holder, SH2-Z manufactured by TOYO Corporation and a liquid evaluation cell were used.

[0260] The liquid evaluation cell was filled with a solvent and placed in SH2-Z, and then connected to an impedance measurement analyzer "MTZ-35" manufactured by Bio-Logic, and measured at a frequency of 1 Hz to 10 MHz.

[0261] The obtained capacitance is set as C1, the battery thickness is set as d, the battery area is set as S, and the dielectric constant of vacuum is set as ε0 = 8.9 × 10 -12 , the relative dielectric constant ε was calculated according to the following formula.

[0262] ε=C1×d / (ε0×S)

[0263] [Method for measuring viscosity]

[0264] TVE-25L manufactured by TOKI SANGYO CO., LTD. and a conical rotor 48'×R24 were used.

[0265] 2 mL of solvent was measured and placed in a measurement container of TVE-25L under a 25°C environment, and the value after rotating at a rotation speed of 100 rpm for 1 minute was defined as viscosity (unit: mPa·s (milliPascal seconds)).

[0266] [Measurement method of reduction potential]

[0267] As an electrolyte for measuring the reduction potential, ethylene carbonate / ethyl methyl carbonate (50 volume % / 50 volume %) containing LiPF6 at a concentration of 1 M was prepared.

[0268] A high dielectric constant and low viscosity solvent was added to the electrolyte solution so as to be 5 mass %, and cyclic voltammetry was performed.

[0269] During the rise of the current value, the voltage at which the difference between the result measured using only the reduction potential measurement electrolyte solution and the result measured with the addition of a high dielectric constant low viscosity solvent became 0.2 mA was defined as the reduction potential.

[0270] The voltage was recorded by changing from the Ag / AgNO3 reference value to the Li / Li+ reference value.

[0271] Measurement equipment: VMP-300 manufactured by Biologic

[0272] Working electrode: Glassy carbon 3mm diameter

[0273] Counter electrode: Platinum black grid

[0274] Reference electrode: Ag / AgNO3 (internal solution: acetonitrile / TBAP) manufactured by BAS: RE-7

[0275] Determination conditions:

[0276] Scanning voltage: -3.6V~-1V (vs Ag / Ag+)

[0277] Scan speed: 5mV / sec

[0278] [Table 1]

[0279]

[0280] *Since it is solid at 25°C, the measurement was performed at 60°C.

[0281] [Preparation of non-aqueous electrolyte]

[0282] A non-aqueous electrolyte (water concentration of 100 ppm or less) was prepared according to the formula shown in the table below, and its ion conductivity was measured as described below. As an electrolyte, LiPF6 was used in E0 to E14, and LiN(FSO2)2 (also described as "LiFSI") was used in E15, and was used at the concentrations shown in the table below. In addition, VC was used as an additive at the concentrations shown in the table below.

[0283] <Measurement of ion conductivity>

[0284] A nonaqueous electrolyte was placed in a four-terminal conductivity battery SB1400 manufactured by EC FRONTIER CO., LTD. and sealed. The battery was measured using VMP-300 manufactured by Biologic under the following conditions to calculate the ion conductivity.

[0285] Measuring temperature 25℃

[0286] Measurement method: 4-terminal measurement AC impedance method

[0287] Frequency: 1MHz~1Hz

[0288] Amplitude voltage: 10mV

[0289] With respect to the obtained resistance value R, the ion conductivity (σ) was calculated according to the following calculation formula based on the electrode area S and the inter-electrode distance L of the battery.

[0290] σ=1 / R×L / S

[0291] [Table 2]

[0292]

[0293] [Example B1]

[0294] <Preparation of positive electrode slurry>

[0295] LiFePO4 (LFP) as a positive electrode active material was mixed in a manner such that 45 volume %, KB as a conductive aid was 2 volume %, and the non-aqueous electrolyte shown in the following table was 53 volume %, and stirred at 1250 rpm for 90 seconds using a centrifugal planetary mixer (manufactured by THINKY CORPORATION: Awatori Rentaro) to obtain a positive electrode slurry.

[0296] <Preparation of negative electrode slurry>

[0297] Artificial graphite as a negative electrode active material was 40 volume %, carbon black as a conductive aid was 1.5 volume %, and the non-aqueous electrolyte shown in the following table was 58.5 volume % and stirred at 650 rpm for 5 minutes using a centrifugal planetary mixer (manufactured by THINKY CORPORATION: Awatori Rentaro) to obtain a negative electrode slurry.

[0298] <Manufacturing of non-aqueous electrolyte secondary batteries>

[0299] The positive electrode slurry prepared above was placed in a plate with a thickness of 500 μm and an area of ​​80 cm 2 The slurry was applied onto an aluminum foil as a positive electrode current collector in a manner of 80 mm in length and 100 mm in width to obtain a positive electrode layer member composed of a laminate of the positive electrode current collector and the positive electrode slurry layer.

[0300] The negative electrode slurry prepared above was prepared to a thickness of 500 μm and an area of ​​87 cm 2 The slurry was applied onto a copper foil as a negative electrode current collector in a manner of 84 mm in length and 104 mm in width to obtain a negative electrode layer member composed of a laminate of the negative electrode current collector and the negative electrode slurry layer.

[0301] Cut the diaphragm shown in the table below into pieces with an area of ​​91 cm 2 (86mm in length and 106mm in width).

[0302] The positive electrode layer component, the separator and the negative electrode layer component are stacked in such a manner that one side of the separator contacts the positive electrode slurry layer and the other side of the separator contacts the negative electrode slurry layer to obtain a stacked body. In order to prevent the volatilization of the electrolyte, the above series of steps are completed within 1 minute.

[0303] Tabs were ultrasonically welded to respective ends of the positive electrode current collector and the negative electrode current collector, wrapped with an aluminum laminate, and sealed with a vacuum sealer, thereby obtaining a nonaqueous electrolyte secondary battery.

[0304] [Examples B2 to B15, Examples B18 to B24, Comparative Examples HB1 and HB2]

[0305] The nonaqueous electrolyte used in the positive electrode slurry and the negative electrode slurry was set as shown in the "Positive Electrode Slurry Layer" and "Negative Electrode Slurry Layer" columns in the following table, the thickness of the positive electrode slurry layer and the negative electrode slurry layer was set as shown in the following table, and the separator shown in the following table was used. Except for this, a nonaqueous electrolyte secondary battery was obtained in the same manner as Example B1.

[0306] [Examples B16 and B17]

[0307] In the preparation of the non-aqueous electrolyte secondary battery of Comparative Example HB2, after preparing a positive electrode layer component consisting of a laminate of a positive electrode collector and a positive electrode slurry layer, acetonitrile was added to the positive electrode slurry layer in a manner such that the acetonitrile concentration in the solvent of the positive electrode slurry layer became 20 mass % (recorded as "post-addition" in the table below), thereby preparing the positive electrode layer components of the non-aqueous electrolytic secondary batteries of Examples B16 and B17.

[0308] Furthermore, in the preparation of the non-aqueous electrolyte secondary battery of Comparative Example HB2, after preparing a negative electrode layer component consisting of a laminate of a negative electrode collector and a negative electrode slurry layer, acetonitrile was added to the negative electrode slurry layer in a manner such that the acetonitrile concentration in the solvent of the negative electrode slurry layer became 20 mass % (recorded as "post-addition" in the table below), to prepare the negative electrode layer components of the non-aqueous electrolytic secondary batteries of Examples B16 and B17.

[0309] The separator used was set as shown in the following table, and a non-aqueous electrolyte secondary battery was obtained in the same manner as in Example B1.

[0310] [Test Example 1]

[0311] The following charge and discharge test was carried out using (TOSCAT3000) manufactured by TOYO SYSTEM CO., LTD.

[0312] <Charge and discharge before test>

[0313] The nonaqueous electrolyte secondary battery produced above was charged and discharged before testing by CC-CV charging under the following conditions and then CC discharging under the following conditions, thereby obtaining a nonaqueous electrolyte secondary battery for testing.

[0314] CC-CV charging conditions: current value 100mA, upper limit voltage 3.9V, termination current value 25mA.

[0315] CC discharge conditions: current value 100mA, termination voltage value 2.0V.

[0316] Furthermore, the nonaqueous electrolyte secondary battery of Example B18 was subjected to CC-CV charging under the following conditions before the above CC-CV charging.

[0317] CC-CV charging conditions: current value 100mA, upper limit voltage 2.4V, charging time 4 hours.

[0318] In this embodiment, the upper limit voltage of 2.4 V corresponds to about 1.5 V as the negative electrode voltage.

[0319] After the above-mentioned charge and discharge before the test, a part of the aluminum laminate was cut to remove unnecessary gas generated during the charge and discharge before the test, and the laminate was sealed again with a vacuum sealer.

[0320] <Cyclic characteristics test>

[0321] The nonaqueous electrolyte secondary battery for the test was subjected to repeated CC-CV charging and CC discharging under the following conditions to examine the cycle characteristics.

[0322] CC-CV charging conditions: current value 250mA, upper limit voltage 3.9V, termination current value 25mA.

[0323] CC discharge: current value 250mA, termination voltage value 2.0V.

[0324] The cycle characteristics were evaluated by applying the number of cycles at which the discharge capacity reached 50% of the discharge capacity in one cycle according to the following evaluation criteria.

[0325] (Evaluation Criteria)

[0326] A: More than 301 cycles.

[0327] B: 201 cycles or more and 300 cycles or less.

[0328] C: 101 cycles or more and 200 cycles or less.

[0329] D: 51 cycles or more and 100 cycles or less.

[0330] E: Less than 50 cycles.

[0331] <Output characteristics test>

[0332] The above-mentioned nonaqueous electrolyte secondary battery for testing was charged under the following conditions and then discharged under the following conditions, and the output characteristics were examined.

[0333] (Base discharge capacity)

[0334] CC-CV charging: current value 250mA, upper limit voltage 3.9V, termination current value 25mA.

[0335] CC discharge: current value 250mA, termination voltage value 2.0V.

[0336] (Large current discharge capacity)

[0337] CC-CV charging: current value 250mA, upper limit voltage 3.9V, termination current value 25mA.

[0338] CC discharge: current value 1000mA, termination voltage value 2.0V.

[0339] The output characteristics were evaluated by applying the discharge capacity retention rate calculated by the following formula to the following evaluation criteria.

[0340] Discharge capacity retention rate (%) = (large current discharge capacity / reference discharge capacity) × 100

[0341] (Evaluation Criteria)

[0342] A: More than 70%

[0343] B: 60% or more and less than 70%

[0344] C: 55% or more and less than 60%

[0345] D: 50% or more and less than 55%

[0346] E: Less than 50%

[0347] The results of each test are shown in the table below. The table below also shows how much additive (VC) in the non-aqueous electrolyte solution used to manufacture the battery remained in the negative electrode slurry layer after charge and discharge before the test (residual amount = additive concentration in the negative electrode slurry layer after charge and discharge before the test, mass %).

[0348] [Table 3]

[0349]

[0350] The details of the separators in the above table are shown below.

[0351] Wet PE: SW320F (trade name, manufactured by Senior)

[0352] Polymer electrolyte 1: Referring to the specification of U.S. Patent Application Publication No. 2020 / 0358107 and J.Am.Chem.Soc.2020, 142, 3301-3305, a polymer electrolyte known as a Li ion hopping conductive polymer electrolyte was prepared to produce a separator. Specifically, according to the Preparation of solid polymer electrolytes item of the supporting information of J.Am.Chem.Soc.2020, 142, 3301-3305, a separator with a thickness of 20 μm was obtained.

[0353] Polymer electrolyte 2: Polyethylene oxide (weight average molecular weight 500,000) and LiFSI manufactured by FUJIFILM Wako Pure Chemical Corporation were used to prepare the following steps. 50 g of polyethylene oxide and 70 g of LiFSI were dissolved in tetrahydrofuran, and then applied to a polytetrafluoroethylene (PTFE) film using a scraper in a manner such that the dry film thickness was 20 μm. After drying, the polyethylene oxide film was peeled off from the PTFE film and used as a separator.

[0354] Inorganic coating PE: SH716W14 (trade name, manufactured by Senior)

[0355] Dry PE: CE2500 (trade name, manufactured by Celgard)

[0356] As shown in the above table, regarding the second embodiment of the manufacturing method of the present invention, when the ratio of the high dielectric constant low viscosity solvent in the solvent of the positive electrode slurry used in the formation of the positive electrode slurry layer is the same as the ratio of the high dielectric constant low viscosity solvent in the solvent of the negative electrode slurry used in the formation of the negative electrode slurry layer, the cycle characteristics of the obtained non-aqueous electrolyte secondary battery are poor (Comparative Example HB1). In addition, when the high dielectric constant low viscosity solvent is not used in the non-aqueous electrolyte, the output characteristics of the obtained non-aqueous electrolyte secondary battery are poor (Comparative Example HB2).

[0357] On the other hand, the nonaqueous electrolyte secondary battery obtained by the production method of the present invention is excellent in all cycle characteristics and also excellent in output characteristics.

[0358] In addition, regarding the second embodiment of the manufacturing method of the present invention, it is known that if a polymer electrolyte that is difficult for the solvent to permeate is used as a separator, it is possible to achieve both cycle characteristics and output characteristics at a higher level. On the contrary, when dry PE that is easy for the solvent to permeate is used as a separator, the cycle characteristics are slightly inferior to the case where wet PE or a polymer electrolyte is used for the separator.

[0359] Furthermore, it was found that in the non-aqueous electrolyte secondary battery obtained by the production method of the present invention, the additive forming a film on the negative electrode easily remained in the electrolyte after the cycle test (compared with Comparative Example HB1).

[0360] [Test Example 2]

[0361] <Manufacturing suitability test>

[0362] The nonaqueous electrolyte used was set as shown in the following table, and the conditions were set as described below. In addition, positive electrode layer components C-1 to C-16 were obtained in the same manner as the preparation of the positive electrode layer components in the manufacture of Example B1. Specifically, after applying the slurry under a dry environment (dew point -40°C, room temperature 25°C), it was transferred to a low temperature environment within 10 seconds, and then placed under low temperature conditions (5°C) for 2 minutes. Then, the surface of the electrode slurry layer was visually observed to investigate the state of cracks or defects, and the manufacturing suitability was evaluated using the following evaluation criteria. If defects occur in the electrode slurry layer, the electrode slurry layer will peel off during stacking in battery production, resulting in a deterioration in the yield. This manufacturing suitability test becomes an indicator of the yield. The results are shown in the table below.

[0363] (Evaluation Criteria)

[0364] A: No cracks or defects were observed.

[0365] B: Slight cracks or chips were observed.

[0366] C: A clear defect is observed at the end.

[0367] [Table 4]

[0368] Positive electrode layer component No. Non-aqueous electrolyte No. Manufacturing suitability C-1 E1 B C-2 E2 C C-3 E3 C C-4 E4 B C-5 E5 B C-6 E6 B C-7 E7 B C-8 E8 B C-9 E9 B C-10 E10 B C-11 E11 A C-12 E12 A C-13 E13 A C-14 E14 A C-15 E15 B C-16 E0 A

[0369] The above results also show that the manufacturing suitability is further improved when a solvent having a relative dielectric constant of 10 or more is used as a high dielectric constant low viscosity solvent. In addition, it is also known that the manufacturing suitability is further improved when propionitrile or isobutyronitrile having a boiling point of 90 degrees or more is used.

[0370] The present invention has been described together with its embodiments, but unless otherwise specified, any details in the description are not intended to limit our invention, and it is believed that it should be widely interpreted without violating the spirit and scope of the invention as shown in the attached claims.

[0371] This application claims priority based on Japanese Patent Application No. 2022-136375 filed in Japan on August 29, 2022, the contents of which are incorporated herein by reference as a part of the description of this specification.

[0372] Explanation of symbols

[0373] 10- non-aqueous electrolyte secondary battery, 1- negative electrode collector, 2- negative electrode active material layer, 3- separator, 4- positive electrode active material layer, 5- positive electrode collector.

Claims

1. A method for manufacturing a non-aqueous electrolyte secondary battery, comprising the following (a1) to (c1): (a1) obtaining a positive electrode layer component, the positive electrode layer component comprising a laminate of a positive electrode current collector and a positive electrode slurry layer, the positive electrode slurry layer being formed by dispersing a positive electrode active material in a non-aqueous electrolyte solution in which at least a portion of the solvent is a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s; (b1) obtaining a negative electrode layer component, wherein: Forming a laminated structure of a negative electrode current collector and a negative electrode slurry layer, wherein the negative electrode slurry layer is formed by dispersing a negative electrode active material in a non-aqueous electrolyte solution in which the solvent is a solvent having a relative dielectric constant of less than 5.0 and / or a viscosity of 2.0 mPa·s or more, and by making the negative electrode slurry layer contain a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s, a negative electrode layer component consisting of a laminate of the negative electrode current collector and the negative electrode slurry layer is obtained; and (c1) forming a stacked structure by stacking the positive electrode layer member, the separator, and the negative electrode layer member so that one side of the separator contacts the positive electrode slurry layer and the other side of the separator contacts the negative electrode slurry layer.

2. A method for manufacturing a non-aqueous electrolyte secondary battery, comprising the following (a2) to (c2): (a2) obtaining a positive electrode layer component, wherein: The positive electrode layer component is composed of a laminate of a positive electrode current collector and a positive electrode slurry layer, wherein the positive electrode slurry layer is formed by dispersing a positive electrode active material in a non-aqueous electrolyte in which a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s accounts for X mass % of the solvent; (b2) obtaining a negative electrode layer component, wherein the negative electrode layer component is composed of a laminate of a negative electrode current collector and a negative electrode slurry layer, wherein the negative electrode slurry layer is formed by dispersing a negative electrode active material in a non-aqueous electrolyte in which the proportion of a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s in the solvent is less than X mass %; and (c2) forming a stacked structure by stacking the positive electrode layer member, the separator, and the negative electrode layer member so that one side of the separator contacts the positive electrode slurry layer and the other side of the separator contacts the negative electrode slurry layer.

3. The method for manufacturing a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein: In the laminated structure formed by the above-mentioned (c1) and (c2), the thickness of the positive electrode slurry layer is 150 μm or more.

4. The method for manufacturing a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein: The solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s includes a compound having at least one of a cyano group, an ester bond, and an ether bond.

5. The method for manufacturing a non-aqueous electrolyte secondary battery according to claim 4, wherein: The compound having at least one of a cyano group, an ester bond and an ether bond is a compound represented by any one of the following formulae (1) to (3), [Chemical formula 1] In the above formula, R 11 ~R 14 represents an alkyl group having 1 to 3 carbon atoms, R 15 represents a hydrogen atom or a fluorine atom, n is an integer from 1 to 3, and in the above formula (2), two R 12 can be connected to each other to form a ring. In the above formula (3), R 13 and R 14 They can be connected to each other to form a ring.

6. The method for manufacturing a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein: In (a1) and (a2), the ion conductivity of the non-aqueous electrolyte constituting the positive electrode slurry layer is set to 12 mS / cm or more.

7. The method for manufacturing a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein: The content of the electrolyte in the nonaqueous electrolyte solution constituting the positive electrode slurry layer in (a1) and (a2) and the content of the electrolyte in the nonaqueous electrolyte solution constituting the negative electrode slurry layer in (b1) and (b2) are set to 0.9 M or more.

8. The method for manufacturing a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein: The nonaqueous electrolyte solution constituting the positive electrode slurry layer in (a1) and (a2) and the nonaqueous electrolyte solution constituting the negative electrode slurry layer in (b1) and (b2) contain an additive that reacts with the surface of the negative electrode active material to form a film.

9. The method for manufacturing a non-aqueous electrolyte secondary battery according to claim 8, wherein: The content of the additive in the nonaqueous electrolyte solution constituting the positive electrode slurry layer and the nonaqueous electrolyte solution constituting the negative electrode slurry layer is set to 2 to 28% by mass.

10. The method for manufacturing a non-aqueous electrolyte secondary battery according to claim 2, wherein: In the negative electrode slurry layer in (b2), the ratio of the solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s in the solvent is set to less than 20 mass %.

11. The method for manufacturing a non-aqueous electrolyte secondary battery according to claim 1 or 2, comprising: After the above (c1) and (c2), CV charging is performed at a potential higher than the reduction potential of the solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s.

12. The method for manufacturing a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein: The positive electrode slurry layer and the negative electrode slurry layer of the obtained non-aqueous electrolyte secondary battery both contained acetonitrile.

13. A slurry for a non-aqueous electrolyte secondary battery, comprising: a non-aqueous electrolyte containing a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s; and an electrode active material.

14. The slurry for non-aqueous electrolyte secondary batteries according to claim 13, wherein The electrode active material is a positive electrode active material, and the ratio of the solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s in the solvent is 8 mass % or more.

15. The slurry for non-aqueous electrolyte secondary battery according to claim 13, wherein The electrode active material is a negative electrode active material, and the proportion of the solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s in the solvent is less than 20 mass %.

16. The slurry for non-aqueous electrolyte secondary batteries according to any one of claims 13 to 15, wherein The content of the electrode active material in the slurry is 40 volume % or more.

17. The slurry for non-aqueous electrolyte secondary batteries according to any one of claims 13 to 15, wherein The solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s includes acetonitrile. 18 . The slurry for a non-aqueous electrolyte secondary battery according to claim 13 , which is used to form an electrode slurry layer of a non-aqueous electrolyte secondary battery.

19. A non-aqueous electrolyte secondary battery, comprising a positive electrode slurry layer, a separator and a negative electrode slurry layer in sequence, wherein: The positive electrode slurry layer is composed of a slurry in which a positive electrode active material is dispersed in a non-aqueous electrolyte solution containing a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s. The negative electrode slurry layer is composed of a slurry in which a negative electrode active material is dispersed in a non-aqueous electrolyte solution containing a solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s.

20. The nonaqueous electrolyte secondary battery according to claim 19, wherein: The solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s contained in the positive electrode slurry layer and the solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s contained in the negative electrode slurry layer both include acetonitrile.

21. The nonaqueous electrolyte secondary battery according to claim 19 or 20, wherein: The ratio of the solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s in the solvent in the positive electrode slurry layer is defined as X. a The mass % is X, and the ratio of the solvent having a relative dielectric constant of 5.0 or more and a viscosity of less than 2.0 mPa·s in the solvent in the negative electrode slurry layer is X. b When mass% meets X a >X b .

Citation Information

Patent Citations

  • Rechargeable lithium-ion secondary battery

    JP2005108835A

  • Nonaqueous secondary battery

    JP2012185938A

  • Nonaqueous electrolyte and nonaqueous secondary battery

    JP2016201308A

  • Lithium-ion battery

    JP2017147222A

  • Braking control device of vehicle

    JP2022136375A